Use of polysorbate 20 and sodium thiosulfate to enhance sewage sludge dewaterability by bioleaching - Jie Zhao (IWA Publishing, 2021)
Dewatering of sludge is a key problem that must be solved in the sewage sludge disposal industry. In this study, a series of process optimization tests were conducted to learn how to improve sludge treatment. The optimum process of sludge leaching treatment was studied in a specially designed 100-L reactor system. Four factors were investigated and nine batches of bioleaching tests were run at three levels of these factors. Orthogonal experiments showed that the effect of sludge return ratio and aeration rate on the sludge moisture content was significant and hydraulic retention time (HRT) had a clear effect, but nutrient types had a reduced effect on the moisture content of sludge. The primary and secondary order of each factor is reflux ratio > aeration rate > HRT > nutrient type. Under the optimal process, three batches of sludge were processed and the moisture content of the filter press cake was reduced to less than 60%, the organic matter content reduced to below 5%, and the concentration of heavy metals (Cu, Zn, Pb, and Cr) was much lower than the agricultural standard limit, which is suitable for landscaping, composting, and incineration power generation and other resource applications.